International Information Security: The Main Threats - I. N. Kokhtyulina (Международная аналитика, 2015)
The article describes principles and methods of using social media as a «soft power 2.0» which is considered as an effective tool to achieve political goals of the state. Particularly increasing today is the risk of destructive informational influence threatening the sovereignty and territorial integrity of any state. As a consequence, individuals and society as a whole are also exposed to negative information impact.